2023
DOI: 10.1002/smll.202304338
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Breathable Thermoelectric Skin Using Multimode Radiative Cooling/Solar Heating Assisted Large Thermal Gradient

Yeongju Jung,
Seongmin Jeong,
Jiyong Ahn
et al.

Abstract: This study proposes a Janus structure‐based stretchable and breathable thermoelectric skin with radiative cooling (RC) and solar heating (SH) functionalities for sustainable energy harvesting. The challenge of the wearable thermoelectric generator arises from the small temperature difference. Thus, this dual‐sided structure maximizes the thermal gradient between the body and the surrounding environment, unlike the previous works that rather concentrate on the efficiency of the thermoelectric generator itself. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The cooling system as a necessity for humans accounts for 10% of global electricity consumption. , This will exacerbate the energy crisis as well as accelerate global warming . Passive daytime radiative cooling (PDRC) as a novel cooling technology has aroused widespread interest among researchers for its electricity-free and environment-friendly cooling mode. PDRC with zero energy input can reflect the incident sunlight (0.3–2.5 μm) to minimize the solar heat gain and radiate heat to the universe (∼3 K) through the atmospheric window (8–13 μm). Over the past years, this technology has emerged as a frontier and a variety of PDRC designs have been reported, such as photonic structures, porous polymer films, , particle-embedded coatings, , and fibers. , Among these, photonic structures exhibit tailored spectrum via tuning the subwavelength structural features, realizing distinctive radiative cooling performance. , Strategies for constructing photonic structures like multilayer stacks, periodic structures, random structures, and bioinspired structures thrive in achieving highly efficient passive radiative cooler . Raman et al first reported a multilayer photonic structure used for radiative cooling with a solar reflectance of 97% and selective emissivity across the atmospheric transparency window.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooling system as a necessity for humans accounts for 10% of global electricity consumption. , This will exacerbate the energy crisis as well as accelerate global warming . Passive daytime radiative cooling (PDRC) as a novel cooling technology has aroused widespread interest among researchers for its electricity-free and environment-friendly cooling mode. PDRC with zero energy input can reflect the incident sunlight (0.3–2.5 μm) to minimize the solar heat gain and radiate heat to the universe (∼3 K) through the atmospheric window (8–13 μm). Over the past years, this technology has emerged as a frontier and a variety of PDRC designs have been reported, such as photonic structures, porous polymer films, , particle-embedded coatings, , and fibers. , Among these, photonic structures exhibit tailored spectrum via tuning the subwavelength structural features, realizing distinctive radiative cooling performance. , Strategies for constructing photonic structures like multilayer stacks, periodic structures, random structures, and bioinspired structures thrive in achieving highly efficient passive radiative cooler . Raman et al first reported a multilayer photonic structure used for radiative cooling with a solar reflectance of 97% and selective emissivity across the atmospheric transparency window.…”
Section: Introductionmentioning
confidence: 99%
“…7−10 Over the past years, this technology has emerged as a frontier and a variety of PDRC designs have been reported, such as photonic structures, 11−13 porous polymer films, 14,15 particleembedded coatings, 16,17 and fibers. 18,19 Among these, photonic structures exhibit tailored spectrum via tuning the subwavelength structural features, realizing distinctive radiative cooling performance. 20,21 Strategies for constructing photonic structures like multilayer stacks, 22 periodic structures, 23 random structures, 24 and bioinspired structures 25 thrive in achieving highly efficient passive radiative cooler.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Concerning materials, researchers are dedicated to developing novel RC materials with high emissivity in the atmospheric window and low absorption of the solar spectrum. This involves the incorporation of various strategies, including the utilization of porous structures, 24 nanomaterials, 25 , 26 , 27 and infrared radiation materials, 28 , 29 , 30 , 31 aimed at maximizing the absorption of energy from the cosmic cold source. Additionally, the optimization of heat transfer materials is considered a key means to enhance power generation efficiency, as efficient heat transfer materials can reduce the heat exchange between the system and the surrounding environment, thus minimizing thermal losses and enhancing energy utilization efficiency.…”
Section: Introductionmentioning
confidence: 99%
“… 34 Moreover, some have proposed the integration of the TEG’s hot side with human body heat sources. 25 , 26 , 27 , 31 Therefore, it is possible to flexibly adjust system parameters and manage heat flow direction based on the specific system structure and application context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation